Study on The Efficiency of Zinc Oxide Solid-State Solar Cells Using Organic Dyes Based on Indolene D102 Dye - Shnain, Firas Adel; Al-Agealy , Hadi J. M.; Moghaddam, Hossain Milani (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
In this work, two carrier concentrations with dye D102 were used in a dye-sensitized solar cell to perform a comparative evaluation of the efficiency and influence on the study of key parameters affecting the device performance. To achieve this goal, the cell transfer power, current, current density and fill factor were calculated to estimate the power conversion efficiency (PCE) of DSSCs. Electrons move from the excited state of indolene D02 to the conduction band of ZnO to produce current for DSSCs through the assumed energy levels of donor indolene and acceptor ZnO in the hetero junction device to be continuous. The effect of carrier concentration and coupling strength on the improvement of the contact efficiency of D102 hetero junction dye with ZnO-based DSSCs is discussed using quantum charge transfer theory. D102-ZnO with ethanol-based DSSCs with PCEs up to (14.368%) were developed and the main J-V properties were investigated, the corresponding carrier concentration efficiency of )1/m3)  is much lower (7.256%) compared to using a concentration of )1/m3)   to reach (14.368%), mainly due to the lower charge transport.